Fostering a Sustainable University in Germany - Setting, Infrastructure and Perspectives - Klaus Rick; Klaus Helling (Universitas Diponegoro, 2025)
Today, circumstances have changed across Europe and the world, sustainable development engagement in politics unfortunately steps back for military investments and more protective and defense spendings. The world is experiencing a rollback in terms of climate protection, sustainable development and scientific freedom. The consequences could have very negative impacts on today’s and future generations. Hence universities worldwide have to concentrate harder and broader on future focused and science based sustainable solutions. So the concept of the Environmental Campus Birkenfeld is not only to instruct and talk about sustainability. We practice very consequently what is taught in the lectures every single day with an advanced infrastructure. Students, lecturers, labs and institutes study and work successfully with a professoral experience in these fields of almost 30 years, researching, testing and installing new environmental engineering technologies, teaching state of the art sustainable business and advanced environmental law. This paper focuses examples of the campus setting regarding facilities and buildings that are equipped technologically on a high level – as the Environmental Campus is Germany’s first zero emission campus and a model site of Trier University. Finally, the ‘UI Green Metric family’ must foster and maintain advanced sites to convince people, politicians and third-party funds to assure the endowment of universities further on. Reducing or even stopping the admission of resources for science and education like in the U.S. 2025 is not acceptable – nowhere. This is a challenge for universities worldwide.